2005
DOI: 10.1163/22941932-90000109
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Microfibril Angle and Stiffness by near infrared Spectroscopy using sample sets having Limited wood Density Variation

Abstract: Near infrared (NIR) spectroscopy offers a rapid method for the estimation of microfibril angle (MFA) and SilviScan-estimated wood stiffness (EL(SS)). The success of these NIR calibrations may be related to airdry density, because density varies in wood simultaneously with MFA and stiffness. The importance of density variation was investigated by developing calibrations for MFA and EL(SS) using Pinus radiata D. Don (radiata pine) and Pinus taeda L. (loblolly pine) sample sets where the density range was small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 11 publications
0
28
2
4
Order By: Relevance
“…Initially NIR focused on properties related to pulping (e.g. Raymond and Schimleck, 2002;Raymond et al, 2001); however, its use has been extended to any other trait that could have a chemical basis; for example wood stiffness and MFA (Schimleck et al, 2005). NIR can also be used to estimate a more general chemical composition (Schimleck et al, 2005), including galactan content, which is related to longitudinal shrinkage (Floyd and Stanish, 2004) and, finally, to dimensional stability of the wood.…”
Section: Phenotypic Informationmentioning
confidence: 99%
“…Initially NIR focused on properties related to pulping (e.g. Raymond and Schimleck, 2002;Raymond et al, 2001); however, its use has been extended to any other trait that could have a chemical basis; for example wood stiffness and MFA (Schimleck et al, 2005). NIR can also be used to estimate a more general chemical composition (Schimleck et al, 2005), including galactan content, which is related to longitudinal shrinkage (Floyd and Stanish, 2004) and, finally, to dimensional stability of the wood.…”
Section: Phenotypic Informationmentioning
confidence: 99%
“…More recent NIR studies of wood are focusing on mechanical properties (Hoffmeyer and Pedersen 1995;Thumm and Meder 2001;Schimleck et al 2005;Fujimoto et al 2008), anatomical characteristics (Schimleck and Evans 2004;Alves et al 2007), physical (Codgill et al 2004;Mora et al 2008;Taylor et al 2008;Hein et al 2009), and chemical properties (Zahri et al 2008;Tyson et al 2009). NIR spectroscopy can also be applied to wood based composites (Campos et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that E L(SS) calibration based on NIR spectra obtained from a set of representative cores could provide excellent predictions of E L(SS) , and the predictions were better than those reported in and Schimleck & Evans (2002b). Schimleck et al (2005b) investigated the possibility of obtaining predictive calibrations for E L(SS) using diffuse reflectance NIR spectra collected in 10 mm sections from the radial longitudinal face of wooden strips where the density range is small and the relationships between E L(SS) and density are poor. The authors concluded that strong calibrations for E L(SS) could be obtained when density variation is limited, and when there are no relationships between density and E L(SS) .…”
Section: Modulus Of Elasticity (Moe) and Nir Applicationmentioning
confidence: 74%
“…Schimleck et al (2005b) investigated the importance of density variation by developing calibrations for MfA using two pine species (P. radiata and P. taeda) samples sets where the density range was small and the relationship between density and MfA was poor. The calibrations for MfA were obtained, especially when sets had densities larger than 500 kg/m 3 .…”
Section: Modulus Of Elasticity (Moe) and Nir Applicationmentioning
confidence: 99%
See 1 more Smart Citation